(untitled) (GYMNASIUM, 2017)
This paper presents the weight of the main means used by athletes from CSM Bacău 2010 during the competitional year 2011-2012 in the preparatory periods. We want to know if the share is different depending on the athletic event practiced and the level of preparation. This study aims, as a general purpose, to highlight the weight of the most effective means of the preparatory periods before the 2011 and 2012 indoor and outdoor seasons, at middle distance runners from the Municipal Sports Club Bacau, 2010. We started from the assumption that the share of the main means used in the preparatory periods of 2011 and 2012 indoor and outdoor seasons for the Municipal Sports Club athletes from Bacau is different depending on the athletic event practiced and the level of preparation. As research methods I used: bibliographic study method, statistical and mathematical methods, evaluation methods (samples). In the study we included five athletes, subjects aged 16-28 years who have achieved national and international level have been analyzed and interpreted. The findings reveal that the share of resources used in the preparatory period October-November 2011 and April-May 2012 was beneficial in obtaining valuable results.